PENERAPAN TOTAL QUALITY MANAGEMENT DALAM MENINGKATKAN SUMBERDAYA MANUSIA - EDWIN AGUS BUNIARTO (Jurnal Akademika, 2015)
In increasing the quality of human resources, corporate can implement total qualitymanagement (TQM), by which an employee should do a job better, more effective and moreefficient in producing the products with high quality and competitive price. The researchaims to identify the implementation process of TQM, and its influence toward the quality ofhuman resources. The result showed the variables of TQM (that is, employees role, employerrole, relations of employer and employees, organizational aspects, and environ employees,organization aspects, and environmental aspects) are simultaneously have a significantinfluence toward the quality of human resources in PR. HF Prima Malang. Theorganizational aspects variable is dominantly influence the corporate’s quality of humanresources.Keywords : Total Quality Management implementation, human resources quality